Opening the Stone Hole Door: The Strategy of the Sorong Regency Tourism Office in the Development of Stone Hole Beach Tourism - Agnes Sombolayuk; Karmila Sinen (Journal of Government Science Studies, 2026)
This study aims to formulate strategies and develop the Batu Lubang tourist destination by considering numerous internal and external factors that influence the development of tourist destinations. This is a descriptive qualitative study. SWOT analysis (Strengths, Weaknesses, Opportunities, Threats) is a strategic planning method used to identify the strengths, weaknesses, opportunities, and threats in an activity or organization. The research results indicate that several key success factors can be identified, including: management of natural resources and natural beauty, improvement and maintenance of supporting tourism facilities, development of adequate accessibility, empowerment of local communities through tourism awareness groups (pokdarwis), the use of information technology and digital promotion, efficient financial management and funding, strategic collaboration with various parties, and risk mitigation and tourism safety. The development of the Batu Lubang Beach tourist destination is influenced by a combination of driving and inhibiting factors. The unique natural attractions, supporting facilities, and active involvement of the local community through the Tourism Awareness Group (Pokdarwis) are the main driving forces behind this destination. However, it is still hampered by limited infrastructure, inadequate facilities, lack of digital promotion, and minimal funding support from the local government. Batu Lubang Beach possesses extremely rich and unique natural tourism potential, which offers opportunities for developing ecotouris attracting tourists, and the role of the local community through the Tourism Awareness Group (Pokdarwis) is crucial. The presence of content from YouTubers and TikTokers further strengthens the promotion of this destination and its tourism appeal.